The Minimum Significant Ratio: A Statistical Parameter to Characterize the Reproducibility of Potency Estimates from Concentration-Response Assays and Estimation by Replicate-Experiment Studies - Eastwood, Brian J.; Farmen, Mark W.; Iversen, Philip W.; Craft, Trelia J.; Smallwood, Jeffrey K.; Garbison, Kim E.; Delapp, Neil W.; Smith, Gerald F. (Journal of biomolecular screening, 2006)
The authors show by illustration that procedures used to validate the reliability of single-concentration high-throughput screens such as the signal window and Z' factor do not ensure sufficient reliability in potency estimates from concentration response assays. They develop the minimum significant ratio as a statistical parameter to characterize the fold change between 2 compounds run in the same experiment that can be considered a real difference and use this parameter to characterize the reliability of the assay. They adapt methods described by Bland and Altman to develop a simple set of 2 experiments to estimate the minimum significant ratio and show that this protocol can identify assays that lack reproducibility. The methods are then extended to validate the equivalency of the same assay run by multiple laboratories.